Initial Study of Students' Critical Thinking Ability Level and Concept Mastery on Earth Structure Material - Yendri Tri Hartati Napitupulu; Sardianto Markos Siahaan; Hamdi Akhsan (Jurnal Penelitian Pendidikan IPA, 2024)
Critical thinking and concept mastery is an important ability for every student to have. So, educators need to get information about the level of skills possessed by student. This study aims to describe the initial level of critical thinking skills and mastery of students' concepts, as well as the relationship between critical thinking skills and mastery of students' concepts on earth structure material in class VIII at SMP Negeri 2 Namang. The methodology used in the research is descriptive quantitative, using a critical thinking ability test and concept mastery test, and qualitative, using interviews. Students' critical thinking and concept mastery tests showed an average score of 43.78 and 55.94, with a fairly low category. The average value of the inference indicator was 25.97, and the indicator of making further explanations was 37.01. Both are the lowest indicators that still need to be improved. In contrast, the average value of the strategy and tactics indicator is 73.95, which is in the high category. The significance value obtained is <0.001, which indicates that there is a strong, significant, and directly proportional relationship between critical thinking skills and concept mastery, with a correlation coefficient value of 0.803. The results of the interview show the low enthusiasm of students in learning the structure of the earth due to the lack of a variety of media used and test questions that are not used to being done.